Visual inspection using acetic acid and pap smear as a method of cervical cancer screening - Vadehra, K.; Jha, R. (Journal of Institute of Medicine Nepal, 2007)
Introduction: The objective of this study was to study the of comparison of visual inspection using acetic acid and pap smear as a method of cervical cancer screening. The specific objectives were to determine the proportion of women screened positive with VIA and proportion of women screened positive with pap smear. Another specific objective was to determine total number of cervical intraepithelial neoplasia and carcinoma cervix in the study population. Method: This was a comparative study. A total of 500 women presenting to the outpatient gynecologic clinic, T.U. Teaching Hospital from23rd February 2004 to 22nd February 2005, who met the inclusion criteria were examined by both conventional cytology and visual inspection using 5% acetic acid. Distinct acetowhite areas touching the transformation zone were categorized as VIA positive cases. ASCUS or worse lesions by cytology were considered as positive smears. Those women who showed positive test result with either VIA or pap smear or both tests were further subjected to colposcopy directed biopsy and histology was taken as gold standard to compare the performance of VIA and cytology. Those for whom histology revealed no pathology or reactive/reparative change or inflammation were considered as false positives. Results: On VIA, 37 out of 500 women screened had acetowhite lesions. On pap smear, 27 out of the 500 women had ASCUS or worse lesions. The proportion of women screened positive with VIA was 7.4%and the proportion of women screened positive with pap smear was 5.4 %. Of the 500 enrolled women, 20 were positive on both VIA and cytology; 17 were positive on VIA only; and 7 were positive on cytology only. So 44 patients had cervical biopsies performed on them. Histological diagnosis of CIN/cancer was made in 28 out of the total 44 patients who underwent biopsy. Incidence of CIN/ cancer cervix in the study population was found to be 5.6 %. Pap smear picked up 20 out of the 28 biopsy-proven cases. The 8 lesions missed by cytology included 5 low grade, 2 high grade and 1 cancer. VIA could identify 27 out of the 28 CIN/carcinoma cervices; the only lesion being missed was LSIL. But VIA had higher number of false positives as compared to cytology. VIA was more sensitive (96.4%) than pap smear (71.4%), which was statistically significant. However, the specificity of VIA was lower (37.5 %) than that of cytology (56.3%). The PPV of VIA was 73% versus 71.4 % for pap smear. The NPV of VIA was 85.7 % versus 52.9 % for cytology. Overall, VIA demonstrated an accuracy of 75 % as compared to 65.9 % for cytology. Conclusion: In women undergoing screening for pre-invasive and cancer cervix, visual inspection using 5 % acetic acid was found to be more sensitive and has a higher accuracy as compared to pap smear. VIA is less specific than cytology, resulting in high false-positive and hence unnecessary referral for colposcopy/biopsy. Although the present study is small, other larger comparative studies have evaluated the validity of VIA as a method of cervical cancer screening and concluded the same. Another important feature of VIA is its high Negative Predictive Value, which means that when the test result is negative, the woman can go home assured that she is not likely to have a neoplastic cervical lesion. Visual inspection is a simple, accurate, cost effective method of rapidly differentiating between a potentially diseased cervix and a healthy one and therefore its use can be recommended as primary screening method. Journal of Institute of Medicine Vol.28(1) 2006